RECOMMENDATIONS ON POETIC TRANSLATION FROM UZBEK INTO ENGLISH LANGUAGE (American Journal of Pedagogical and Educational Research, 2023)
In this article we have focused on various methods of translation, characteristically, direct method in poetry translation, its peculiarities and advantages. As we have chosen poetry translation, we tried to give some recommendation on poetry from Uzbek into English language.